A study of cases of bisphosphonate-induced cholesteatoma of the external auditory canal - NAKASHIMA, Toshiyuki; SHIN, Takemoto; SHUTO, Hiroyuki (jibi to rinsho, 2021)
Although osteonecrosis of the external auditory canal has been known to be a serious side effect of bisphosphonates, there are still few case reports on this condition. Bisphosphonates, are bone resorption inhibitors that are a first-line drug for osteoporosis and metastatic bone cancer. In Japan, where the population is rapidly aging, the number of people taking bisphosphonates will probably continue to increase. We experienced 10 cases of bisphosphonate-induced cholesteatoma of the external auditory canal. In addition, we compared our cases to 19 previously reported cases according to the clinical progression classification. In both groups, the condition most frequently developed in elderly women who had been treated with bisphosphonates for a long time. The degree of progression and the duration of administration showed an inverse correlation, and it was found that even if the duration of administration was long, the condition did not necessarily progress. Regardless of the degree of progression, there were many cases of unilateral onset, and there was a tendency for the condition to frequently develop on the inferior and anterior inferior walls of the external auditory canal. Epithelialization was obtained in all cases with local treatment only; however, in the previously reported cases, the post-treatment course was not constant according to the treatment or degree of progression. It is expected that the accumulation of further cases of bisphosphonate-induced cholesteatoma of the external auditory canal will lead to the establishment of medical guidelines; however, at the present time, otolaryngologists should check whether patients take bisphosphonates, strive for early detection and discuss treatment strategies as needed in collaboration with orthopedic surgeons or physicians.